The effect of cardiac rehabilitation on left ventricular diastolic functions assessed by exercise stress echocardiography in patients with acute coronary syndrome - YAĞCI, İLKER (My University, 2024)
Objective: The aim of our study is to investigate the impact of cardiac rehabilitation on left ventricular (LV) diastolic function in acute coronary syndrome (ACS) patients. Patients and Methods: Patients were selected consecutively among ACS patients who underwent primary percutaneous intervention and were found eligible for cardiac rehabilitation program from May 2014 to May 2015. Forty-four patients were included in cardiac rehabilitation group and recruited to 30 sessions of Phase 3 cardiac rehabilitation program six weeks after discharge. Twenty consecutive patients were included as control group. LV diastolic functions were assessed by resting and stress echocardiography. Results: There were not any significant differences in characteristics between the groups. Resting and stress E velocities and resting lateral e’ velocity significantly increased after rehabilitation program. Left atrial volume index, resting and stress A velocities and average E/e’ ratios were significantly lower while stress lateral e’ velocity was significantly higher in rehabilitation group after program compared to controls. The number of patients with diastolic dysfunction decreased after rehabilitation program. Final resting and stress echocardiography revealed significantly lower frequency of diastolic dysfunction in rehabilitation group. Conclusion: Cardiac rehabilitation improves diastolic functions in ACS patients, which may be detected by stress echocardiography. Keywords: Acute coronary syndrome, Cardiac rehabilitation, Diastolic function, Diastolic stress echocardiography
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; Clinical Medicine (MED); CLINICAL MEDICINE; Acute coronary syndrome; Cardiac rehabilitation; Diastolic function; Diastolic stress echocardiography